Sm16, A Schistosoma mansoni Immunomodulatory Protein, Fails to Elicit a Protective Immune Response and Does Not Have an Essential Role in Parasite Survival in the Definitive Host - Wilma Patrícia de Oliveira Santos Bernardes; Juliano Michel de Araújo; Gardênia Braz Carvalho; Clarice Carvalho Alves; Aline Thaynara de Moura Coelho; Isabela Thamara Sabino Dutra; Sueleny Silva Ferreira Teixeira; Rosy Iara Maciel de Azambuja Ribeiro; Marina de Moraes Mourão; Rosiane Aparecida da Silva-Pereira; Cristina Toscano Fonseca (Journal of Immunology Research, 2019)
Sm16 is an immunomodulatory protein that seems to play a key role in the suppression of the cutaneous inflammatory response during Schistosoma mansoni penetration of the skin of definitive hosts. Therefore, Sm16 represents a potential target for protective immune responses induced by vaccination. In this work, we generated the recombinant protein rSm16 and produced polyclonal antibodies against this protein to evaluate its expression during different parasite life-cycle stages and its location on the surface of the parasite. In addition, we analyzed the immune responses elicited by immunization with rSm16 using two different vaccine formulations, as well as its ability to induce protection in Balb/c mice. In order to explore the biological function of Sm16 during the course of experimental infection, RNA interference was also employed. Our results demonstrated that Sm16 is expressed in cercaria and schistosomula and is located in the schistosomula surface. Despite humoral and cellular immune responses triggered by vaccination using rSm16 associated with either Freund’s or alum adjuvants, immunized mice presented no reduction in either parasite burden or parasite egg laying. Knockdown of Sm16 gene expression in schistosomula resulted in decreased parasite size in vitro but had no effect on parasite survival or egg production in vivo. Thus, our findings demonstrate that although the vaccine formulations used in this study succeeded in activating immune responses, these failed to promote parasite elimination. Finally, we have shown that Sm16 is not vital for parasite survival in the definitive host and hence may not represent a suitable target for vaccine development.